Effect of hydroxyurea on SP1, LIN28B, IGF2BP3, COL4A5, BCL2, gamma globin genes expression: an in vitro study - Akram Agha-Amini Fashami; Esmat Alemzadeh; Hossein Safarpour; Ebrahim Miri-Moghaddam (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background In some β-thalassemia intermedia patients, hydroxyurea (HU) increases hemoglobin and HbF levels. However, HUs’ effects molecular mechanism is still unclear. Methods In this study, a weighted gene co-expression network analysis was conducted on the GSE109186 dataset. The genes LIN28A, COL4A5, SP1, BCL2, and IGF2BP3 were identified as hub genes involved in the γ-gene switching process. The effect of HU treatment at doses of 50, 100, and 150 μM for 12, 24, and 48 h on the K562 cell line was examined by using qRT-PCR to measure the expression levels of these hub genes. Results SP1 gene expression decreased after treatment with 50, 100, and 150 μM HU for 12, 24, and 48 h. The expression of the LIN28A gene was tripled at three concentrations of 50, 100, and 150 μM for 12 h. The IGF2BP3 gene expression was doubled after 24 and 48 h at a concentration of 150 μM HU. Regarding COL4A5 gene expression, except at 12 h after treatment at a concentration of 50 μM, a significant increase was observed in other concentrations and times. The BCL2 gene expression pattern at all concentrations decreased significantly after 12 h. The γ gene showed a significant increase compared to the control group after 24 and 48 h at the different concentrations. Conclusion The results showed that in HU-treated cells, changes in the expression of LIN28A, COL4A5, SP1, and IGF2BP3 genes were accompanied by an increase in γ-gene expression. By elucidating precisely the mechanism of γ-to-β gene switching, we can hope for less complicated drugs.